The molar tooth sign and the bat wing appearance in Joubert syndrome - Dorigatti Soldatelli, Matheus; Henz Concatto, Natália; Morales Saute, Jonas Alex; Fischinger Moura de Souza, Carolina; Adams Perez, Juliano; Ávila Duarte, Juliana (Clinical and Biomedical Research, 2018)
A 10-year-old female patient was brought to the outpatient clinic with a history of neurodevelopmental delay, gait and limb incoordination, and oculomotor apraxia. According to her parents, the girl had always showed delayed acquisition of motor milestones when compared to other children, which became more evident when she was 8 months old and was not able to sit. She was able to sit by age of 2, and walked independently, but unsteady, when she was 3.5 years old. She presented with cognitive impairment. Reviewing her history, it became clear that she was hypotonic at birth and subsequently developed gait ataxia in early childhood. She was born to nonconsanguineous parents and there were no other similar cases in her family. On physical examination, she held her head preferentially in a lateralized position to her right side. She showed gait ataxia in tandem walking, abnormal stance with a positive Romberg’s sign, dysmetria, dysdiadochokinesia, diffuse hyperreflexia, bilateral Babinski sign, and oculomotor apraxia. The Wechsler Intelligence Scale for Children-III (WISC-III) demonstrated an IQ of 67 (intellectual disability). There were no other abnormalities on physical examination. Electroencephalogram showed focal paroxysmal discharges of moderate intensity in the posterior parietal-temporal region. Brain magnetic resonance imaging (MRI) demonstrated agenesis of the cerebellar vermis with a slit in the medial line sparing the two cerebellar hemispheres (Figure 1), lengthening and thickening of the cerebellar peduncles, associated with reduction of the anteroposterior diameter of the mesencephalon, the so-called “molar tooth sign” (MTS) (Figure 2). Morphological alterations in the posterior fossa showed a 4th ventricle with a typical “bat wing” appearance (Figure 3). These findings were highly suggestive of Joubert syndrome (JS).